2015
DOI: 10.1097/mca.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the neutrophil-to-lymphocyte ratio in patients with non-ST-segment elevation myocardial infarction

Abstract: The present study demonstrated an independent association between race and NLR in patients with NSTEMI, suggesting that a tailored cutoff value according to race would provide more precise prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(46 reference statements)
4
1
0
Order By: Relevance
“…Another study evaluated 3738 consecutive patients undergoing elective and urgent coronary angiography and demonstrated a significant independent association between NLR and the presence and severity of coronary artery disease [6]. Our study also shows an increased incidence of coronary artery disease with increasing tertiles of NLR, and similar to other reports in populations with and without vascular disease shows a lower NLR in Black non Hispanic individuals [7][8]. The current report is one of the very few studies to evaluate an all-comers population of patients with PAD undergoing delineation of peripheral arterial anatomy on angiography.…”
Section: Discussionsupporting
confidence: 89%
“…Another study evaluated 3738 consecutive patients undergoing elective and urgent coronary angiography and demonstrated a significant independent association between NLR and the presence and severity of coronary artery disease [6]. Our study also shows an increased incidence of coronary artery disease with increasing tertiles of NLR, and similar to other reports in populations with and without vascular disease shows a lower NLR in Black non Hispanic individuals [7][8]. The current report is one of the very few studies to evaluate an all-comers population of patients with PAD undergoing delineation of peripheral arterial anatomy on angiography.…”
Section: Discussionsupporting
confidence: 89%
“…NLR may vary according to age, sex and race. 42 , 43 , 44 In our study NLR increased with age: NLR group 1 (≤5.25) had mean age of 59.4 ± 11.3 and NLR group 2 (NLR > 5.25) with their mean age of 62.51 ± 13.11. Difference of mean age in both group was statistically significant ( p < 0.02).…”
Section: Discussionsupporting
confidence: 50%
“…In our study, patients were divided in two groups based on cut-off value of NLR 5.25 which provided highest predictive power of mortality (sensitivity of 89.36%: 95% CI, specificity of 75.07%: 95% CI, positive predictive value of 32.4% and negative predictive value of 98.1%). NLR may vary according to age, sex and race 42, 43, 44. In our study NLR increased with age: NLR group 1 (≤5.25) had mean age of 59.4 ± 11.3 and NLR group 2 (NLR > 5.25) with their mean age of 62.51 ± 13.11.…”
Section: Discussionsupporting
confidence: 44%
“…Until now, many studies have been conducted in the literature regarding the prognostic value of parameters such as WBC count, monocyte count, neutrophil count, neutrophil/lymphocyte ratio, Monocyte/Lymphocyte ratio in patients with acute coronary syndrome (18)(19)(20)(21)(22). In our study, we observed that these parameters were parallel to the literature data in patients with NSTEMI and we also witnessed a statistically significant relationship with AgNOR proteins.…”
Section: Discussionsupporting
confidence: 81%